Photodetection Properties of Nonpolar a‐Plane GaN Grown by Three Approaches Using Plasma‐Assisted Molecular Beam Epitaxy. Issue 18 (17th July 2019) - Pant, Rohit Kumar; Singh, Deependra Kumar; Roul, Basanta; Chowdhury, Arun Malla; Chandan, Greeshma; Nanda, Karuna K.; Krupanidhi, Saluru B.
Abstract : Present work focuses on improving the quality of nonpolar a‐plane GaN thin films by introducing unconventional new efficient growth conditions without compromising their UV photodetection properties. These epitaxial thin films are grown on r‐plane sapphire using three different growth approaches by plasma‐assisted molecular beam epitaxy (PAMBE). In situ reflection high‐energy electron diffraction (RHEED) analysis is performed during and after the growth to monitor the growth mode, and it is found that the films assumed desired 2D mode during the growth. The crystalline quality and the phase purity of the films are assessed with the help of high‐resolution X‐ray diffraction and Raman spectroscopy. All the films are found to contain compressive stress, which indicate that all the films are strained and epitaxial. The temporal response is carried out in all the three batches, which is very stable. Sensitivity, responsivity, transit time, and gain values are estimated. Highest responsivity and the corresponding gain are found to be around 25 AW −1, 86.47 at 1 V bias, respectively. These are the highest reported values so far for a‐plane GaN at such low voltages. Abstract : UV‐A radiation is significantly transmitted by the atmosphere, and this phenomenon makes photodetection of UV‐A very important. Nonpolar a‐GaN is grown with three different approaches by plasma‐assisted molecular beam epitaxy, and interdigitated electrode‐based photodetectors are processed. Highest responsivity and the corresponding gain are estimated around 25 AW −1 and 86.47 at 1 V bias, respectively. These are the highest reported values so far for a‐plane GaN at such low voltages.